From Unmasking towards Building. A Post-Critical Perspective in Educational Research - Zamojski, Piotr (INSTED: Interdisciplinary Studies in Education & Society, 2014)
The article aims at questioning the critical paradigm in social sciences, and within, in educational research. Starting from the reconstruction of its main assumptions and the critical arguments against this paradigm I try to conceptualise a possibility of post-critical perspective in educational research with reference to the work of J. Ranci?re, A. Badiou and G. Biesta. The essence of this post-critical perspective I claim to be the practice of building, which requires a shift from philosophy of emancipation to philosophy of responsibility to be undertaken. The practice of building is understood as an intervention of a pedagogue into a social status quo, and is conceptualised with reference to the radical social constructivism of symbolic interactionism.